Dynamic Left Ventricular Outflow Tract Obstruction Exacerbated by Thoracic Kyphosis - Mohamad S. Alabdaljabar, MBBS; Mackram F. Eleid, MD (JACC: Case Reports, 2023)
We present a 74-year-old woman with kyphosis and symptoms of pre/syncope. Heart catheterization revealed dynamic left ventricular outflow tract obstruction (DLVOTO) with Brockenbrough Braunwald response only when kyphotic posture was assumed. She had a positive response to metoprolol. DLVOTO is a challenging diagnosis in the absence of resting LVOTO. (Level of Difficulty: Beginner.)